Neutral or factor saving innovations? (2018)
We present a theoretical argument to identify the conditions under which a firm prefers to invest in factor saving innovations rather than neutral innovations. We prove that incentives to invest in factor saving innovations positively depend on i) total factor productivity and ii) the scarcity of the factor.